Motivasi Belajar Siswa MI Terhadap Pelajaran Bahasa Arab - Sulastri, Tyara; Purba, Gita Rahmayani; S, Sapri; Falah, Abdul Syahir; Rizqi, Ika Husnul; Wardiyah, Rizky; Siregar, Sarah Syafitri; Nur Rizki, Syafira (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article aims to describe students' learning motivation, as well as examining how Learning Motivation influences MI students' Arabic language lessons at MIN 6 Medan City. The research method used is a qualitative method in the form of literature study and field study. With data collection techniques in the form of interviews, observations and document studies. The results of the research show that motivation greatly influences the interest of MI students, especially in MIN 6 Medan City, in studying Arabic. From the observation results, it was found that students who have high learning motivation will obtain better learning compared to students who have low learning motivation. So in improving the learning outcomes of a subject, efforts are needed to increase student motivation.